How adolescents cope with food insecurity in Baltimore City: an exploratory study. Issue 12 (August 2019) - Mmari, Kristin; Offiong, Asari; Gross, Susan; Mendelson, Tamar
Abstract: Objective: To increase our understanding about food insecurity among urban adolescents, we conducted a qualitative study in Baltimore City with adolescents to: (i) explore how adolescents experience and cope with food insecurity; and (ii) identify community-based approaches or interventions for addressing food insecurity. Design: A total of eight focus groups were conducted across six neighbourhoods. To gather sociodemographic characteristics and personal data on food insecurity, all consented adolescents completed a brief questionnaire. Setting: Six purposively selected neighbourhoods in Baltimore City, USA. Participants: A total of fifty-three adolescents between the ages of 14 and 19 years participated in the study. Results: Although half of our sample was classified as food insecure, everyone in the focus groups was aware of adolescents who engaged in risky behaviours to get money for food. Among girls, prostituting was the most commonly mentioned behaviour, whereas for boys, it was selling drugs or stealing to get money for food. Adolescents also described tremendous stigma associated with food insecurity and agreed that food insecurity has to be viewed within a broader set of economic challenges. Conclusions: Addressing food insecurity among adolescents in disadvantaged neighbourhoods should be a high priority for policy makers and practitioners. Current feeding programmes are not addressing the needs of adolescents; as a result, adolescents are at risk for a variety of harmful behaviours and outcomes, with long-term negative health and social consequences.